Bridal Dais of the Iranun Community in the District of Kota Belud, Sabah: (Pelamin Masyarakat Iranun di Daerah Kota Belud, Sabah) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
This article aims to study the material culture or tools used for showcasing the beauty of the bridal dais of the Iranun, an ethnic minority that occupies, particularly, the coastal areas at Kota Belud and several villages in Lahad Datu. The study looks at the beauty of Iranun bridal dais, which symbolizes the social values or authority structure in its social system, from the point of view of material culture. This study was conducted through fieldwork employing the observational method and interviews. The location under study included three villages in the Kota Belud area, comprising Kampung Payas-Payas, Kampung Pantai Emas and Kampung Peladuk. Eight informants were interviewed using the unstructured interview method to document the material culture of the Iranun with respect to bridal dais. The study reveals that artefacts are important in order to maintain social status among the Iranun, while at the same time displaying the uniqueness of this ethnic minority, who continue to practice the culture inherited from their forebears to this very day.Keywords: Iranun, Kota Belud, material culture, bridal dais, social status.